High-pressure pool-boiling heat transfer enhancement and mechanism on engineered surfaces - Dahariya, Smreeti (Kansas State University, 2020)
Boiling has received considerable attention in the technology advancement of electronics cooling for high-performance computing applications. Two-phase cooling has an advantage over a single-phase cooling in the high heat removal rate with a small thermal gradient due to the latent heat of vaporization. Many surface modifications have been done in the past including surface roughness, mixed wettability and, porous wick copper play a crucial role in the liquid-vapor phase change heat transfer. However, the mechanisms of high-pressure pool-boiling heat transfer enhancement due to surface modifications has not been well studied or understood. The properties of water, such as the latent heat of vaporization, surface tension, the difference in specific volume of liquid and vapor, decrease at high-pressure. High-pressure pool-boiling heat transfer enhancement is studied fundamentally on various engineered surfaces. The boiling tests are performed at a maximum pressure of 90 psig (620.5 kPa) and then compared to results at 0 psig (0 kPa). The results indicate that the pressure influences the boiling performance through changes in bubble dynamics. The bubble departure diameter, bubble departure frequency, and the active nucleation sites change with pressure. The pool-boiling heat transfer enhancement of a Teflon© coated surface is also experimentally tested, using water as the working fluid. The boiling results are compared with a plain surface at two different pressures, 30 and 45 psig. The maximum heat transfer enhancement is found at the low heat fluxes. At high heat fluxes, a negligible effect is observed in HTC. The primary reasons for the HTC enhancement at low heat fluxes are active nucleation sites at low wall superheat and bubble departure size. The Teflon© coated surface promotes nucleation because of the lower surface energy requirement. The boiling results are also obtained for wick surfaces. The wick surfaces are fabricated using a sintering process. The boiling results are compared with a plain surface. The reasons for enhancements in the pool-boiling performance are primarily due to increased bubble generation, higher bubble release frequency, reduced thermal-hydraulic length modulation, and enhanced thermal conductivity due to the sintered wick layer. The analysis suggests that the Rayleigh-critical wavelength decreases by 4.67 % of varying pressure, which may cause the bubble pinning between the gaps of sintered particles and avoids the bubble coalescence. Changes in the pitch distance indicate that a liquid-vapor phase separation happens at the solid/liquid interface, which impacts the heat-transfer performance significantly. Similarly, the role of the high-pressure over the wicking layer is further analyzed and studied. It is found that the critical flow length, λᵤ reduces by three times with 200 μm particles. The results suggest that the porous wick layer provides a capillary-assist to liquid flow effect, and delays the surface dry out. The surface modification and the pressure amplify the boiling heat transfer performance. All these reasons may contribute to the CHF, and HTC enhancement in the wicking layer at high-pressure.
Keywords: Critical heat flux; Heat transfer coefficient; Thermal-hydraulic; Rayleigh-Critical Wavelength; Pinning mechanism; Capillary pressure